(untitled) (Bioresearch Communications, 2023)
Caulerpa spp; is a remarkably potential seaweed due to its pharmacological importance, high nutritional compositions, biological activities , and human health benefit. It is a species of ulvophyte green algae inhabiting mostly in the intertidal and shallow sub-tidal coastal regions in the Asia- Pacific and commonly consumed in South-East Asia for its high contents of vitamins and minerals. Besides its culinary uses, it is well-reported for its antibacterial, antifungal, diabetes, blood pressure, and lipid-lowering properties. However, to date, no extensive assessment of the diversity, distribution, and biological activity assay of these seaweeds found on the Bangladesh coast has been carried out. This study aimed at anti-inflammatory and analgesic studies of 50% ethanolic extract of Caulerpa racemosa. collected from St. Martin’s Island, Bangladesh. Consequently, secondary metabolites such as steroids, flavonoids, glycoside, and saponin were also detected in the phytochemical assay. In the present study, 25 & 50mg/kg body weight of ethanolic extract of C. racemosa was used in hot plate, acetic acid, formic acid, and carrageenan-induced paw edema in Swiss albino mice showing C. racemosa extract has significant analgesic and anti-inflammatory properties. Bioresearch Commu. 9(2): 1330-1339, 2023 (July)